Горнозаводские моногорода России - Боярко Г. Ю. Григорий Юрьевич; Матюгина Э. Г. Элеонора Григорьевна; Пожарницкая О. В. Ольга Вячеславовна; Гринкевич Л. С. Лариса Сергеевна (2017, 2017)
Заглавие с экрана